Universal Embedded Motor Control - Modrack, Daniel; Nilsson, Christoffer (My University, 2014)
Brushless DC motors have become more and more popular in recent years, mainly due to their high power density and their potentially very simple control. To demonstrate their bene cial characteristics, a universal platform for motor control has been constructed. Di erent commutation algorithms are implemented on a digital signal controller and their performance is evaluated. A simulation model is created and tested for various commutation schemes. For user interaction, a graphical interface is adapted to the motor. An automatic test mode that measures relevant motor parameters for the control is developed. Using the created models and the real hardware, di erent control algorithms are discussed and compared.
Keywords: Data- och informationsvetenskap; Computer and Information Science